Euro area macro-financial stability: A flow-of-funds perspective - Günter W. Beck; Hans-Helmut Kotz; Natalia Zabelina (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
The global financial crisis (as well as the European sovereign debt crisis) has led to a substantial redesign of rules and institutions - aiming in particular at underwriting financial stability. At the same time, the crisis generated a renewed interest in properly appraising systemic financial vulnerabilities. Employing most recent data and applying a variety of largely only recently developed methods we provide an assessment of indicators of financial stability within the Euro Area. Taking a "functional" approach, we analyze comprehensively all financial intermediary activities, regardless of the institutional roof - banks or non-bank (shadow) banks - under which they are conducted. Our results reveal a declining role of banks (and a commensurate increase in non-bank banking). These structural shifts (between institutions) are coincident with regulatory and supervisory reforms (implemented or firmly anticipated) as well as a non-standard monetary policy environment. They might, unintendedly, actually imply a rise in systemic risk. Overall, however, our analyses suggest that financial imbalances have been reduced over the course of recent years. Hence, the financial intermediation sector has become more resilient. Nonetheless, existing (equity) buffers would probably not suffice to face substantial volatility shocks.
urn:nbn:de:hebis:30:3-390627
Keywords: 330; bank and non-bank financial intermediation; shadow banking; financial stability; systemic risk; financial regulation